2015
DOI: 10.1111/sji.12325
|View full text |Cite
|
Sign up to set email alerts
|

Doubly ReactiveINSIGF2 Autoantibodies in Children with Newly Diagnosed Autoimmune (type 1) Diabetes

Abstract: The splice variant INS-IGF2 entails the preproinsulin signal peptide, the insulin B-chain, eight amino acids of the C-peptide and 138 unique amino acids from an ORF in the IGF2 gene. The aim of this study was to determine whether levels of specific INS-IGF2 autoantibodies (INS-IGF2A) were related to age at diagnosis, islet autoantibodies, HLA-DQ or both, in patients and controls with newly diagnosed type 1 diabetes. Patients (n = 676), 0-18 years of age, diagnosed with type 1 diabetes in 1996-2005 and controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The fusion of a tumor-associated gene and a pancreas-related gene, INS-IGF2, probably participates in PC progression and invasion specifically. Recently, such fusion gene INS-IGF2 is reported to be specifically expressed in pancreatic islets especially in patients with autoimmune diseases under pathological conditions [ 147 , 148 ]. Since immune response is quite significant for tumor surveillance, INS-IGF2 is definitely associated with the unique tumor-associated immune response and may further contribute to the prognosis of pancreatic cancer [ 148 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fusion of a tumor-associated gene and a pancreas-related gene, INS-IGF2, probably participates in PC progression and invasion specifically. Recently, such fusion gene INS-IGF2 is reported to be specifically expressed in pancreatic islets especially in patients with autoimmune diseases under pathological conditions [ 147 , 148 ]. Since immune response is quite significant for tumor surveillance, INS-IGF2 is definitely associated with the unique tumor-associated immune response and may further contribute to the prognosis of pancreatic cancer [ 148 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 illustrates that the EBV epitope-derived pentapeptides are widespread among the most disparate human proteins able to cause, when altered, a vast spectrum of diseases, from diabetes and sterility to myocarditis and death, 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 the latter two being possibly associated with the Titin imposing peptide sharing (250 shared pentapeptides).…”
Section: Resultsmentioning
confidence: 99%
“…4), although conclusions regarding protein expression can not be made, this indicates that the INS-IGF2 chimeric protein may be expressed. Although the precise function of the INS-IGF2 protein remains unidentified, kanatsuna et al (30,31) recently found INS-IGF2 to be recognized by autoantibodies associated with diabetes mellitus type 1 (DM1). In DM1, pancreatic β-cells are destroyed due to the recognition of pancreatic islets autoantigens, like insulin, by autoreactive T lymphocytes leading to a T-lymphocyte-mediated immune response (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of several autoantibodies towards these pancreatic islets autoantigens is a sign of autoimmunity (32). The authors therefore suggested that INS-IGF2 may enhance the ability of insulin to trigger the development of DM1 (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation